D-dimer and factor VIIa in atrial fibrillation – prognostic values for cardiovascular events and effects of anticoagulation therapy - Siegbahn, Agneta; Oldgren, Jonas; Andersson, Ulrika; Ezekowitz, Michael D.; Reilly, Paul A.; Connolly, Stuart J.; Yusuf, Salim; Wallentin, Lars; Eikelboom, John W. (Thrombosis and Haemostasis, 2016)
Coagulation markers may improve monitoring the risk of stroke and bleeding in patients with atrial fibrillation (AF) during anticoagulant treatment. We examined baseline levels of D-dimer and their association with stroke, cardiovascular death and major bleeding in 6,202 AF patients randomised to dabigatran or warfarin in the RE-LY trial. The effects of treatment on serial levels of D-dimer and coagulation factor (F) VIIa in 2,567 patients were also analysed. Baseline D-dimer levels were related to the rate of stroke/systemic embolism (SEE) with 0.64 % in the lowest quartile (Q1, as reference) (D-dimer < 298 μg/l), 1.38 % Q2 (D-dimer 298–473 μg/l), 1.71 % Q3 (D-dimer 474–822 μg/l) and 2.00 % in Q4 (D-dimer > 822 μg/l) (p=0.0007). Similar associations were shown for cardiovascular death and major bleeding. Addition of baseline D-dimer to established clinical risk factors improved prediction of stroke/SEE, cardiovascular death and major bleeding (C-index increased from 0.66 to 0.68, 0.71 to 0.73 and 0.66 to 0.67, respectively). Dabigatran provided a greater reduction of D-dimer levels than warfarin regardless of baseline anticoagulant treatment. Ontreatment levels of FVIIa were markedly reduced by warfarin (median 12.1–13.8 mU/ml) but significantly higher with dabigatran (median 39.4–49.0 mU/ml) at all-time points. Dabigatran is associated with greater reduction in D-dimer without the pronounced reduction of FVIIa seen with warfarin. These different effects on the coagulation system might explain the better efficacy and less intracranial bleeding observed with dabigatran compared with warfarin.Clinical Trial Registration: NCT00262600 (www.clinicaltrials.gov).Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Atrial fibrillation; anticoagulants; D-dimer; FVIIa; stroke